(untitled) (Czech Journal of Multidisciplinary Innovations, 2022)
This article is devoted to the history of the scientific direction of hamzashunoslik, which is a component of the science of Uzbek literary science, the history of the study of the dramatic works of Hamza Hakimzadeh Niyazi, the founder of Uzbek drama.